Mic drop a high-rise mystery - Jackson, Sharna (Knights Of, 2020)
It's October half-term and pop star, TrojKat is filming a music video in the The Tri, the high-rise block home to slueths Nik and Norva. When tragedy strikes the famous singer under mysterious circumstances, Nik and Norva set out to solve the case, with their friend George, and their impressive detective skills. The sequel to HIGH-RISE MYSTERY, another whodunnit in the phenomenal mystery series by Sharna Jackson
Sequel to High-rise mystery
Keywords: Schwester; Popsängerin; Detektiv; Sozialwohnung; Mord; Abenteuer; Schwarze; London; Großbritannien; Kinderbuch